Strategi Promosi Produk Asuransi Jiwadi PT Prudential Syariah Cabang Binjai - Sakinah Sakinah; Yusrizal Yusrizal (UNIVED Press, 2023)
Business competition in today's modern era is increasing and also fierce, where every company is required to carry out attractive promotional strategies in order to get and attract customers. In this case, researchers are interested in researching sharia insurance products, namely life insurance. Which is where the purpose of this study is to find out what promotional strategies can be used by companies to attract customers. Because promotion is very necessary for the company because on the one hand it convinces consumers of the products offered, while on the other hand it determines the success of the company in facing competition in the market. In the context of business competition, each company makes maximum efforts to implement marketing strategies in order to increase product sales and maintain its name and market share.